Fighting the Hydra - Tjorven Harmsen; Ina Hennen; Marie Kaltenbach (Journal of Dynamic Decision Making)
Crises today occur in manifold variants. Cyberattacks, floods, wars, pandemics – the list of cases is ongoing. Academic literature recognizes them as “transboundary crises” (Ansell et al. 2010) or as “global polycrisis” (Homer-Dixon et al., 2022), referring to their transgressing, cascading and overlapping dynamics in both space and time. In this paper, we discuss how decisions are made at a local level in such dynamic, if not disruptive, environments. By combining DDM and crisis management literature, we illustrate how the decision-making evolves when the crisis shows transboundary characteristics, that is, when cascading dynamics call for even more decisions (hence the “Hydra” metaphor referring to a monster in Greek mythology that multiplies its heads once it is being fought). The paper draws on a qualitative study on decision processes in local authorities and organizations in Germany during the Covid-19 pandemic. It can show (1) how these local actors build inter-organizational networks (e.g. task forces) in order to synchronize their decision processes against the background of changing federal requirements; (2) how, due to the duration of the pandemic, rather permanent decision systems developed; and (3) how these networks learn to sustain dynamic decision-making capacities in order to cope with crises following Covid-19, such as the effects of the war in the Ukraine or recent climate impacts. With these findings we contribute to an “integrative” conception of crisis in current crisis management literature that seeks definition in a dynamic process view rather than using either objective or subjective criteria. A DDM approach allows for a more detailed realization of this conceptual shift by representing the current “cascading disasters” as “cascading decision-making”. This understanding focuses on the active role decision-making plays as well as it reflects on the fact that decision-making in today’s crises always involves others making decisions, too.